ANALISIS PENGELOLAAN PIUTANG DALAM MENINGKATKAN PROFITABILITAS PADA PT KIMIA FARMA TRADING AND DISTRIBUTION CABANG PEKANBARU - Desi Monita; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the level of accounts receivable turnover that occurs on the profitability of PT Kimia Farma Trading And Distribution Pekanbaru Branch Period 2012-2018. This study takes data in the form of financial statements consisting of balance sheets and income statements from 2012-2018. The analytical tool used in this study is the accounts receivable turnover ratio and profitability ratios, including ROI (Return On Investment), ROE (Return On Equity) and NPM (Net Profit Margin). The results of the analysis can be illustrated that the company is less efficient in conducting business. This can be seen from developments that accounts receivable turnover and profitability tend to fluctuate from year to year.              Based on the results of the analysis of researchers it can be concluded that it is known that accounts receivable turnover tends to decrease which results in profitability also decreases.  Keyword: Account Receivable Turn Over, Return On Investment (ROI), Return On Equity (ROE) And Net Profit Margin (NPM).